Paródia e mecanismo mimético em Perdição: exercício sobre Antígona, de Hélia Correia - Pimentel, Samarkandra Pereira dos Santos (2014)
in this dissertation we analyze the drama Perdição: Exercício sobre Antígona (1991), by the portuguese writer Hélia Correia, considering the way by which the writer rewrites and renew the mythological characters and the miths addressed in her play. Her construction suggests some sort of anxious appeal to continuity, as pointed out by Longino on Homer's influence exercised on all thinkers, since Correia s plot begins exactly after sophoclean Antigone s death, in the underworld. However, while reading the play we perceive that Helia makes use of the tools of her craft in not so clear manners. The continuity appears but under the form of parody, which, according to Hutcheon (1988), may also make a tribute to the preceding text, since to include irony and play is never necessarily to exclude seriousness of purpose in postmodernist art . From this, we arrive that we must analyze this drama in the light of René Girard s theory on mimetic desire, envy, and the scapegoat mechanism. The ingenuous criticism in Perdição comes by re-elaborating the characters that expose in their collision human actions and relations that make plain the mimetic mechanism, based in Girard s ritualistic-sacrificial approach, revealing thus how the way by which we lose senses or let somebody s (or even our) blood spill for something as derisory as the kydos, the supreme and nonexistent object in dispute (GIRARD, 2008, p.192), can be banal.